Examining the substrate scope of transaminase variants derived from Vibrio fluvialis - Peel, Christopher (2019)
This work builds on previous work from the O’Reilly group. Bulky ketoenone and diketone substrates structurally preorganised to undergo cyclisation after transamination were synthesised and tested with a panel of transaminases. Particular attention was paid to transaminases engineered for the acceptance of large bulky derivatives of acetophenone, produced by Prof. Uwe Bornscheuer’s group (University of Graz, Austria). These were H3-RAV (L56V/W57C/F85V/V153A) derived from Vibrio fluvialis and 3FCR (Y87F/Y152F/Y59W/T231A) from Rugeria sp. Tests using these enzymes with the bulky ketoenones were unsuccessful, prompting further computational analysis of these transaminases. In silico studies were performed on H3-RAV and used to create a small library of rationally designed mutants increasing space and hydrophobicity at three positions in the enzymes active site; CYS 57, ARG 415 and VAL 422. These mutants were tested on the previously synthesised bulky ketoenone substrates to no avail. The produced mutants gave valuable insight into the roles CYS 57 and ARG 415 play in the stabilisation of aromatic substrates in the active site of H3-RAV. In an attempt to examine the in silico identified positions to exhaustion, directed evolution by iterative saturation mutagenesis was performed. To enable this endeavour, a novel high throughput screen was produced based on the consumption of isopropyl amine (IPA) during transamination and could be measured spectrophotometrically. Mass spectrometry and screening results from the analysis of biotransformations using the ISM produced mutants suggests a small amount of activity for the desired substrates was installed. This activity was not significant enough for quantitative analysis via GC-FID, indicating only trace conversion had been achieved.